Citrus waste derived nutra-/pharmaceuticals for health benefits: Current trends and future perspectives. (January 2018) - Mahato, Neelima; Sharma, Kavita; Sinha, Mukty; Cho, Moo Hwan
Graphical abstract: Highlights: Citrus wastes are rich in phytochemicals, viz., phenolics, flavonoids, etc. Citrus bioactive compounds are antioxidant, antimicrobial, anticarcinogenic, etc. Citrus derived compounds can be used as nutra-/pharmaceuticals. Abstract: Citrus are one of the most widely cultivated fruit crops. Citrus fruits are rich source of essential vitamins, minerals, fibers and bioactive phytochemicals, such as alkaloids, carotenoids, nitrogenous compounds and polyphenolics. The by-products derived from citrus wastes are considered to be an economic and renewable source for valuable compounds which can be used in pharmaceutical, nutraceutical, food and cosmetic industries. The review presents a detailed description on the recent advances with emphasis on the citrus derived nutraceuticals as potential source for various biological properties and physiological roles, such as anti-carcinogenicity, anti-mutagenicity, anti-allergenicity, anti-ageingactivitiy, and natural as well as important constituent in synthetic antioxidants. A comprehensive description on the citrus derived food and drinks as well as nutritious feed for animals has also been included.